ANALISIS PENINGKATAN KUALITAS PELAYANAN PUBLIK BIDANG PENDIDIKAN DI FKIP UNPATTI - OHELLO, MARLON ELFIANUS; SELANNO, HENDRY (Patria Artha University, 2024)
This study aims to evaluate and analyze the improvement of public service quality in thefield of education, which includes physical evidence, responsiveness, reliability, empathy,and confidence in FKIP UNPATTI. This research uses a qualitative approach withinformants from academic service staff and FETT UNPATTI students. Data werecollected through observation, interviews, and documentation, then analyzed usingqualitative methods, including data reduction, data presentation, data verification, andconclusion drawing.The results showed that improving the quality of educational serviceswas seen from various aspects. The repair and improvement of physical facilities, theappearance of staff and lecturers, and the condition of non-operational campus facilitiesshowed a significant increase. Staff responsiveness in serving students is considered quitegood although not yet optimal. Service reliability still needs to be improved, with frequentcomplaints about the speed of service. Empathy from employees towards students isconsidered quite high, with efforts to provide motivation in the teaching and learningprocess. In addition, the guarantee of student data storage has also been wellimplemented by employees at FKIP UNPATTI.